Konstytucyjna ochrona godności jako reakcja na przeszłość totalitarną i zabezpieczenie demokracji w przyszłości - Stefanicki, Robert (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The constitutional protection of dignity is not only an adequate response of European states to the totalitarian past, but also a mechanism for securing society for the future through democratic systemic structures. The German example confirms this. In theoretical-legal constructions concerning dignity, it is given a character that is fundamental to the whole order, and it is usually perceived as the source of its natural-legal conception. The interpretation of the constitutional norm contained in Art. 1 of the German Constitution, similarly to Art. 30 of our Polish Constitution, is constantly evolving, because the scale of threats and their scope change, which creates new challenges and the need to react at the level of one country, but also to secure appropriate standards on an international scale. Discussions on the liberalization of the execution of the sentence, the constitutionalization of the provisions on extraordinary measures, as well as the radicalization of movements related to the creation and activation of terrorist groups and the problem of today’s intensified religious conflicts have created new challenges for science and jurisprudence. Nowadays, there are problems with the development of technologies that were not taken into account at the time of establishing the Constitution, and where the failure to secure ethical boundaries may pose a real threat to human dignity.
Keywords: godność człowieka; autorytaryzm; totalitaryzm; suwerenność państwa; suwerenność ludu; prawa człowieka; demokratyczny porządek prawa